Multicriterial optimization of communication means - Bezruk, V.; Chebotaryova, D.; Skoryk, Y. (IEEE, 2022)
Mathematical models of selection of optimal design variants of systems taking into account a set of quality indicators on the basis of multicriteria approach are given. Application of methods of finding Pareto-optimal design solutions and narrowing of the Pareto subset to the only preferred option in solving problems of nominal planning of mobile communication systems of different generations, planning of mobile transport network and choice optimal speech codecs for IP telephony networks are considered. Also use the theory of Analytic Hierarchy Process for solving problems to choose an optimal variant.
Keywords: Mobile communication; Mathematical models; Speech codecs; Costs; Conferences; Telephony; Market research